PURCHASE DECISIONS ANALYSIS WITH SEVERAL FACTORS - Winda , Winda; Maupa, Haris (International Journal of Application on Economics and Business, 2023)
In today's era, competition between businesses is becoming very tight, especially in the food sector. So that every company must be able to find its potential in order to maintain its business. The aims of this research to determine the influence of price, Word-of-Mouth, and service quality on purchase decisions. The theory used in this research is Price, Word-of-Mouth, Service Quality, and Buying Decision. Data was collected by distributing questionnaires to 100 respondents. The data was collected using a non-probability sampling technique using purposive sampling. The results of the analysis show that price and service quality have a positive effect on buing decision. Word-of-Mouth is the most influential variable over perceived value and service quality on buying decision. From this study, it is evident that the Word-of-Mouth variable is the most influential variable on buying decision, so the company must be able to maintain the Word-of-Mouth.